Chronic Pelvic Pain and Infertility Resulting from Unrecognized Retained Laminaria - Wesley Nilsson; Sasha Mikhael; Jennifer Kaplan (Case Reports in Obstetrics and Gynecology)
Background. In 2013, the abortion rate in the United States was found to be 200 abortions per 1,000 live births. Of these, the CDC estimates that nearly 49% were performed using unsafe measures. Even when these procedures are safely performed, patients are at risk for immediate or delayed complications. In second-trimester terminations, mechanical dilation with an osmotic dilator is common to allow for delivery of the fetus. The Japanese seaweed Laminaria japonica is used to achieve this purpose. Case. A 28-year-old primigravida presented with chronic pelvic pain and infertility. She had irregular menstrual cycles and reported scant yellow discharge. A transvaginal ultrasound revealed an abnormally appearing endometrium with an elongated structure suspicious for a foreign body. The patient reported a voluntary termination of pregnancy twelve years earlier, for which laminaria were placed prior to the dilation and extraction. She underwent an operative hysteroscopy confirming our suspicion for retained laminaria. The pathology report demonstrated chronic severe endometritis and plant based material. Conclusion. Retained laminaria are associated with chronic pelvic pain and chronic infertility. Since they can be difficult to detect on conventional imaging, proper counting prior to insertion and after removal is an essential physician responsibility.